2003
DOI: 10.1039/b210293e
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopy of hydrated benzene cluster cations, [C6H6-(H2O)n]+ (n = 1–6): Structural changes upon photoionization and proton transfer reactions

Abstract: Infrared (IR) spectra of benzene-(water) n cluster cations (Bz-W n ) + (n ¼ 1-6) in the OH and CH stretching vibrational region were observed in order to investigate their structure and reactivity. The cluster cations were prepared by two different production methods: one is due to collision between bare benzene cations and water clusters; and the other utilizes resonance enhanced multiphoton ionization (REMPI) of neutral clusters. The former method prefers the production of the most stable isomer cluster cati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
116
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(130 citation statements)
references
References 42 publications
11
116
2
1
Order By: Relevance
“…Details of the experimental apparatus have been described elsewhere 29 and only brief description is given here. Protonated mixed clusters were produced by pulsed discharge of the TMA/H 2 O mixed vapor seeded in the Ar buffer gas (total pressure of 5 atm).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Details of the experimental apparatus have been described elsewhere 29 and only brief description is given here. Protonated mixed clusters were produced by pulsed discharge of the TMA/H 2 O mixed vapor seeded in the Ar buffer gas (total pressure of 5 atm).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…14,17,18 The latter scenario corresponds to the onset for the formation of an H-bonded solvent network. The global minimum structure corresponds to the cis-BZH + -(H 2 O) 2 structure, cw2-1, in which a H-bonded (H 2 O) 2 dimer binds to the OH proton of cis-BZH + in a linear fashion (Fig.…”
Section: B [Bz-(h 2 O) 2 ]H + Trimer (N = 2)mentioning
confidence: 99%
“…As the PA of (H 2 O) n clusters increases substantially with cluster size n (Table I), often intracluster proton transfer from AH + to the water solvent network occurs above a critical cluster size, n ≥ n c . 8,[14][15][16][17][18] Electronic excitation of AH + ions often has a drastic effect on the PA of A. As a consequence, excited state proton transfer to or from the solvent cluster may be triggered by electronic excitation depending on whether the PA of A decreases or increases upon electronic excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Tanabe et al [4] investigated the O-H stretching vibrations of jet-cooled phenol and phenol-(H 2 O) n (n = 1-3) complexes by IR-UV double-resonance spectroscopy. Miyazaki et al [5] observed the infrared (IR) spectra of benzene-(water) n cluster cations (Bz-W n ) ? (n = 1-6) in the O-H and C-H stretching vibrational regions.…”
Section: Introductionmentioning
confidence: 99%
“…One example in the biological system is that intramolecular hydrogen bonding is partly responsible for the secondary, tertiary, and quaternary structures of proteins and nucleic acids. In particular, hydrogen-bonded organics-water clusters have been investigated intensively in recent years from the experimental and the theoretical points of view [2][3][4][5][6][7][8][9][10]. For instance, He et al [2,3] studied the water complexes of m-, p-, and o-aminobenzoic acid using two-color resonantly enhanced multiphoton ionization (REMPI) and UV-UV holeburning spectroscopy.…”
Section: Introductionmentioning
confidence: 99%